Management and Manufacture of Natural Honey Processing Machines in Kapuas Hulu, West Kalimantan - Komarudin, Udin; Nuraeni Suryaman, Nia; Farida, Ida; Prasetia, Adhita (International Journal of Psychosocial Rehabilitation, 2020)
Honey is one of the potential non-timber forest product commodities that is found in the Kapuas Hulu district of West Kalimantan. Forest Honey is a superior product, where no less than 80 to 100 tons of pure forest honey are produced annually from this region. So to improve the quality of honey that meets the standards (SNI) it is necessary to develop a Honey Processing Machine. In general, natural honey produced by the community does not meet the standards, especially manure and water content that is still 30% (Standard max 20%). Making Natural Honey Processing Machine needs to be done to improve the quality of honey, namely by carrying out a filter (Filter) and the process of reducing water content through heating and vacuum (Evaporator), without reducing the mineral content of honey. The results show that with this machine honey yields are cleaner and the water content becomes 16% (according to the standard)